Предложения по предотвращению и ликвидации повреждений сердечников статоров турбогенераторов - Шевченко, Валентина Владимировна; Лизан, Игорь Ярославович (Донецкий национальный технический университет, 2015)
Состояние отечественного электрооборудования электростанций, в частности, турбогенераторов, требует постоянного контроля их параметров, сервисного обслуживания и реабилитации. Указанные работы выполняются с использованием статистических данных о причинах отказов турбогенераторов. В работе проведена оценка наиболее частых причин отказов и предложены способы реабилитации крупных турбогенераторов с целью продления срока их эксплуатации в случае установления возможности восстановления.

Condition of domestic turbogenerators demands the constant control of parameters, technical maintenance and rehabilitation. The works to assess the status of turbogenerators is carried out using statistical data on the reasons for their failure. The paper shows the evaluation of the most frequent causes of failures of turbogenerators and proposes methods of rehabilitation for prolongation of their exploitation, if it was established that they can be restored. The task was to identify the scientific, technical and informational factors and criteria by which we can determine the energy units, which are primarily in need of modernization and which are inappropriate to rehabilitate by economic reasons. The paper presents data about the number of failures in the turbogenerators of Ukrainian NPPs for the period from 2004 to 2014. It has been established that in the last years namely stator core are the main cause of failures of turbogenerators. The urgency determining the state of stator core of turbogenerators therefore has increased, especially in the end of the core. The results of this analysis are used to develop technical solutions on improving reliability of turbogenerators when working with enlarged power factor and reactive power consumption. The paper considers the causes of destruction of cores of the stator and the reasons decreasing their monolithic condition. The methods of early detection of these conditions and decreasing their harm are proposed.
Proposals on the prevention and elimination of defects in the cores of turbogenerators stators
Keywords: турбогенераторы; электрооборудование; электростанции; сервисное обслуживание; сердечник статора; электромеханическое усилие; зубцовая зона; давление прессовки; turbogenerator; electrical equipment; power station; service maintenance; stator core; electromechanical force; perforated zone; pressure compacts